The Teachers’ Perception on Challenges and Strategies upon CALL Practice in EFL Secondary Classroom - Azizah, Rizki; Hepy Adityarini,; Yeny Prastiwi, (Jurnal Sosial Humaniora, 2024)
CALL draws attention for teachers’ EFL classroom due to its captivating power for enhancing language learning. Several studies prove that CALL is extremely able to promote learners’ skills, yet, there are some obscures ideal practices. The study aims at investigating teachers’ perception on challenges and strategies on CALL practice in the EFL secondary classroom. This study utilises qualitative methods with oral semi-structured interview as the data collection. It involves 6 English teachers who have accustomed their teaching with CALL. They possess different teaching experiences, school infrastructures, and setting ; 2 urban public school, 1 suburban public school, 2 urban private school, and 1 suburban private school. The data are analysed through three phases for ensuring demanded results which can depict challenges and strategies on the basis of teachers’ perception. It results that teachers encounter challenges on insufficient school facilities, inadequate lesson time, unfavourable instructional culture, and disproportionate technological competence. Pertaining to the strategies, they recommend the fulfilment of school facilities, plan-b design, and forum group discussion among teachers. As the summary, this study has deemed a light on how technology is integrated through CALL in EFL Secondary Classroom that eventually brings about preventive action plan for granting the desired outcome. The teachers’ perception might depend on their background knowledge related to the issue, their current workplace, and teaching experiences.